2019
DOI: 10.1186/s12889-019-6500-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of time to cure on multi-drug resistance tuberculosis patients in Amhara region, Ethiopia

Abstract: BackgroundMultidrug-resistant tuberculosis (MDR-TB) is caused by bacteria that are resistant to the most effective anti-tuberculosis drug. The MDR-TB is an increasing global problem and the spread of MDR-TB has different recovery time for different patients. Therefore, this study aimed to investigate the recovery time of MDR-TB patients in Amhara region, Ethiopia.MethodA retrospective study was carried out in seven hospitals having MDR-TB treatment center of Amhara region, Ethiopia from September 2015 to Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…resulting in reduced oxygen exchange and respiratory insufficiency. MDR-TB patients with clinical complications also experience longer recovery times and poor response to TB-medications [31,35]. The relationship between a low BMI and risk of death has been noted in several studies worldwide [24,28,34,[36][37][38] and has been strongly linked to poor nutritional status, which was evident in over 70% of our patient cohort.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…resulting in reduced oxygen exchange and respiratory insufficiency. MDR-TB patients with clinical complications also experience longer recovery times and poor response to TB-medications [31,35]. The relationship between a low BMI and risk of death has been noted in several studies worldwide [24,28,34,[36][37][38] and has been strongly linked to poor nutritional status, which was evident in over 70% of our patient cohort.…”
Section: Discussionsupporting
confidence: 55%
“…Patients with acute lung complications had a higher risk of death as a consequence of infection of the lower respiratory tract leading to the accumulation of inflammatory exudate in the alveoli resulting in reduced oxygen exchange and respiratory insufficiency. MDR-TB patients with clinical complications also experience longer recovery times and poor response to TB-medications [31, 35]. The relationship between a low BMI and risk of death has been noted in several studies worldwide [24, 28, 34, 3638] and has been strongly linked to poor nutritional status, which was evident in over 70% of our patient cohort.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Then, 347 articles were screened by title and abstract. The full-text screening was conducted for 58 articles, and 17 articles that fulfilled the eligibility criteria were included in the final analysis (Ketema et al, 2019;Molie et al, 2019;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019;Tola et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018;Tulu and Kahissay, 2014) (Table 1 and Figure 1). All of the studies were hospital-based retrospective cohort studies conducted among patients with DR-TB treated under TICs found in different parts of the country.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The poor treatment outcome is the share of different risk factors. Among the risk factors are being HIV positive, the weight of the patient, age of the patient, presence of other comorbidities or co-infections, smoking, alcohol, patient condition, delay to start treatment, resistance to more than two anti-TB drugs and involvement of TB outside the lungs are reported (Chung-Delgado et al, 2015;Ketema et al, 2019;Bajehson et al, 2019;Balabanova et al, 2016;Chingonzoh et al, 2018;Khan et al, 2015;Farley et al, 2011;Li et al, 2016;Makhmudova et al, 2019;Kurbatova et al, 2012;Bei et al, 2018;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%